Antifragile: things that gain from disorder - "Taleb, Nassim Nicholas" (New York, 2014)
In The Black Swan, Taleb showed us that highly improbable and unpredictable events underlie almost everything about our world. Here Taleb stands uncer?tainty on its head, making it desirable, even necessary. The antifragile is beyond the resilient or robust. The resil?ient resists shocks and stays the same; the antifragile gets better and better. Just as human bones get stronger when subjected to stress and tension, many things in life benefit from stress, disorder, volatility, and turmoil. What Taleb has identified and calls antifragile are things that not only gain from chaos but need it in order to survive and flourish. Antifragile is a blueprint for living in a Black Swan world. Erudite, witty, and iconoclastic, Taleb's message is revolutionary: the antifragile, and only the antifragile, will make it.
Keywords: Uncertainty (Information theory)-Social aspects